2022
DOI: 10.3389/fmed.2022.805425
|View full text |Cite
|
Sign up to set email alerts
|

Actinic Cheilitis — From Risk Factors to Therapy

Abstract: Actinic cheilitis or solar cheilosis is considered a precursor of malignancy or even an in situ squamous cell carcinoma (SCC) of the lip, located most frequently on the lower lip. Actinic cheilitis (AC) has a higher likelihood of developing into invasive SCC of the lip, which is one of the deadliest non-melanoma skin cancers. Risk factors include chronic UV exposure, increasing age, male gender, fair phototypes, chronic scarring, immunosuppressive therapy, and tobacco use. From a clinical point of view, AC is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
0
8
0
3
Order By: Relevance
“…Additional risk factors include male sex as well as geographic latitude. 26 We found that basophilic collagen degeneration was significantly closer to dysplastic epithelium with a higher risk of malignancy.…”
Section: Discussionmentioning
confidence: 65%
“…Additional risk factors include male sex as well as geographic latitude. 26 We found that basophilic collagen degeneration was significantly closer to dysplastic epithelium with a higher risk of malignancy.…”
Section: Discussionmentioning
confidence: 65%
“…Similar to AK, AC is a precancerous lesion caused by prolonged sun exposure or UVR that is most commonly on the lower lip along the vermilion border. Other risk factors include increasing age, especially over 60 years, working outdoors for more than 25 years, or a history of NMSC ( 37 ). The prevalence of AC is higher in people with fair skin and in areas with high UV exposure near the equator.…”
Section: Discussionmentioning
confidence: 99%
“…У больной установлены факторы риска развития актинического кератоза: II фототип кожи по Фитцпатрику, отягощенный профессиональный и солнечный анамнез (постоянная работа на открытом воздухе -работница сельскохозяйственного труда, фотопротекцию в течение жизни не использовала), признаки хронического фотоповреждения кожи (трофические изменения кожи, актинический эластоз) [2,3,[5][6][7][8][9][10][11][12][13][14].…”
Section: Discussionunclassified
“…К факторам риска возникновения актинического кератоза и актинического хейлита относят: избыточное кумулятивное ультрафиолетовое излучение; профессиональную деятельность и профессиональные вредности; отягощенный солнечный анамнез; I и II типы фоточувствительности кожи по Фитцпатрику; актинические поражения кожи и рубцы; генетические заболевания; рентгеновское и/или инфракрасное излучение; иммуносупрессию и иммунодефицитные состояния; низкий социально-экономический статус пациента; курение [1][2][3][5][6][7][8][9][10][11][12][13].…”
unclassified
See 1 more Smart Citation